Zmiany gospodarcze regionu na przykładzie Andaluzji w okresie przystępowania Hiszpanii do struktur europejskich - Szołek, Krzysztof (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In contemporary analysis of regional development in Poland especially essential are processes connected with European integration. There are searched appropriate objects for comparisons that could reflect prospects of changes in Polish regions in the European Union. In this context very interesting is development of less-developed regions after European accession. This paper is an attempt to point out chosen phenomena and tendencies in Andalusia after joining Spain the European Union. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 27-35